Scaffold-based articular cartilage repair. - Capito, R.M.
Future prospects wedding gene therapy and tissue engineering. In this article, current clinical procedures for articular cartilage repair are reviewed in the context of the contributions that tissue engineering approaches can make in improving the outcome. Specific attention is directed toward the promising effects of growth factors and the potential advantages of employing gene therapy techniques in combination with three-dimensional (3-D) scaffolds. New data are presented to demonstrate the utility of nonviral transfection methods for the transfer of genes to cells in order to induce the synthesis of'desired growth factors. The combination of genes and tissue engineering scaffolds for a sustained localized production of growth factors at cartilage defects is a promising advance that could further improve the outcome of cartilage repair procedures in the future.
Keywords: Articular cartilage repair; Cartilage repair procedures; Cells; Gene therapy; Growth factors; Scaffold-based articular cartilage repair; Tissue engineering; Tissue engineering scaffolds